Penerapan Terapi Realitas untuk Meningkatkan Penerimaan Diri Orang Tua Korban Kekerasan Seksual di PPPAPPKB Fakfak - Pellupesi1Rohayanti; Putri, Roza Elmanika; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Experience as a parent with a child who is a victim of sexual violence at the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning in Kab. Fakfak, West Papua, that they are currently experiencing is an unpleasant experience for them. Being a byword in the environment with current conditions, as parents who fail to educate their children, some of them withdraw from the environment, hiding children who are victims of sexual violence by not continuing their studies and locking them up at home. There are also parents who do not believe their children’s stories if they become victims of sexual violence. In addition, parents become angry and do not like the perpetrators who abused their children, so they want the perpetrators to get a life sentence. Parents cannot accept feelings of failure in educating children, lack of attention to children, and self-blame for what happened to their children and all matters related to this incident. These things reflect unrealistic parental self-acceptance. The reactions of these parents can affect their condition and behaviour towards their children. Acceptance by parents will affect their behaviour towards their children.